MXene/RGO composite aerogels with light and high-strength for supercapacitor electrode materials. (June 2020) - Shao, Liang; Xu, Juanjuan; Ma, Jianzhong; Zhai, Bingyan; Li, Ying; Xu, Ran; Ma, Zhonglei; Zhang, Guohong; Wang, Caiyun; Qiu, Jianhui
Abstract: The existence of inevitable hole defects in the hydrothermal process of graphene hydrogels makes the strength of the prepared aerogel to be further improved. We design a simple self-assembly method of standing at room tempreture for preparing MXene/RGO composite aerogel. The strong forces from different directions make this three-dimensional (3D) porous aerogel unique fusiform shape and stiffer wall of the pores to exhibit favorable strength of 16.18 MPa and excellent cyclic compression performance at a load capacity up to 10 kg (2 MPa). And as a freestanding supercapacitior electrode, it shows excellent electrochemical energy storage performance of 233 F g −1 at 1 A g −1 with an outstanding cycling performance of 91.01% after 10, 000 cycles. Besides, this research lays a certain theoretical reference for free-standing supercapacitor electrode materials. Highlights: MXene/RGO 3D porous composite aerogels were prepared at room temperature with a high strength. The MXene/RGO composite aerogels showed excellent mechanical strength of 16.18 Mpa. The aerogel free-standing electrode exhibited outstanding cycling performance.